Improving Residency Education on Chronic Pain and Opioid Use Disorder: Evaluation of CDC Guideline-Based Education. (17th February 2020) - Raheemullah, Amer; Andruska, Neal; Saeed, Maryam; Kumar, Pardeep
Abstract: Background: National surveys show that primary care physicians feel responsible for addressing the opioid epidemic. They feel their training in managing chronic pain and addiction was insufficient, and commonly endorse the need for more residency training in these areas. However, residency training in these areas remains low, with a lack of faculty expertise and time as the most commonly cited barriers for improvement. Objective: To evaluate the feasibility of an educational program for chronic pain management and addiction that does not rely on faculty expertise or additional time, and assess resident opioid-prescribing practices and confidence in managing chronic pain after its implementation. Methods: A 16-week educational curriculum was incorporated into existing residency didactics. Internal medicine residents attended six educational sessions in 2016 over a 16-week period and implemented a protocol based on CDC Guidelines for Prescribing Opioids for Chronic Pain. Surveys were completed pre- and post-intervention. Results: Implementation of this educational intervention was feasible. Surveys showed improvement in resident confidence in detecting and managing addiction and improved prescribing practices and adherence to CDC recommendations. Conclusion: This pilot study demonstrates that increasing residency education in managing chronic pain and opioid use disorder is feasible, and no longer needs to be postponed due to lack of time or faculty expertise.